2022
DOI: 10.1158/1535-7163.mct-21-0320
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Mediates PSMA/mGluR1-Driven Resistance to the DS-7423 Dual PI3K/mTOR Inhibitor in PTEN Wild-type Prostate Cancer Models

Abstract: Prostate cancer remains a major cause of male mortality. Genetic alteration of the PI3K/AKT/mTOR pathway is one of the key events in tumor development and progression in prostate cancer, with inactivation of the PTEN tumor suppressor being very common in this cancer type. Extensive evaluation has been performed on the therapeutic potential of PI3K/AKT/mTOR inhibitors and the resistance mechanisms arising in patients with PTEN mutant background. However, in patients with a PTEN wild type phenotype, PI3K/AKT/mTO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…[47] Germline mutations associated with other cancers (such as those in PTEN and BRCA1) are also associated with an increased risk. [64] The link between PC and a family history of breast cancer, specifically due to the BRCA1 and BRCA2 gene mutations, has been established. [22,23] Clinicians need a low threshold to investigate PC risk in men with a family history of breast cancer.…”
Section: Genementioning
confidence: 99%
“…[47] Germline mutations associated with other cancers (such as those in PTEN and BRCA1) are also associated with an increased risk. [64] The link between PC and a family history of breast cancer, specifically due to the BRCA1 and BRCA2 gene mutations, has been established. [22,23] Clinicians need a low threshold to investigate PC risk in men with a family history of breast cancer.…”
Section: Genementioning
confidence: 99%
“…13 It should be noted that only PI3K/Akt/mTOR pathway is a critical carcinogenic pathway involved in tumorigenesis and progression in a wide variety of tumours, including PCa, 14 non-small cell lung cancer, 30 breast cancer, 31 lung cancer 32 and colorectal cancer 33 Previous studies have revealed that this pathway is associated with various cellular functions in PCa, such as cell proliferation, migration, invasion, apoptosis and autophagy. 15,34 Therefore, we hypothesized that RPL22L1 may promote PCa progression through PI3K/Akt/mTOR pathway. Our results suggested that RPL22L1 regulated the phosphorylation of several key molecules of PI3K/Akt/mTOR pathway, including p-PI3K, p-AKT and p-mTOR.…”
Section: Rpl22l1 Contributes To Pca Progression Through Pi3k/akt/mtor...mentioning
confidence: 99%
“…Various molecular mechanisms contribute to the progression of PCa, among which PI3K/Akt/mTOR pathway is one of the primary causes 14,15 . PI3K/Akt/mTOR pathway has been reported to be related to the formation and progression of PCa, biochemical recurrence after radical prostatectomy, and drug‐resistance 16,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,11,13 The inhibition of the PI3K/mTOR pathway has resulted in reduced cell survival and tumor growth, accompanied by apoptosis induction, as evidenced by various studies. 10,11,14 Consequently, many researchers have focused on developing and producing dual PI3K/mTOR inhibitors.…”
Section: Introductionmentioning
confidence: 99%